A system for evaluating ferromagnetic object and a method therefor - Misron, Norhisam; Ng, Wei Shin; Raja Othman, Raja Nor Firdaus Kashfi (2012)

(untitled)
The present invention relates to a system (100) for evaluating ferromagnetic objects (10). The system (100) comprises a magnetic sensing unit (50), a magnetic signal acquisition unit (150), and a magnetic signal processing unit (250). The system (100) comprises a magnetic sensing unit (50) having a plurality of magnetic-field generating components (20), and a plurality of magnetic-field sensing components (30) that operate with the magnetic-field generating components (20). The magnetic-field generating component (20) is for generating magnetic field; during the evaluation. The ferromagnetic object (10) is adapted to relatively travel under magnetic flux (210) generated by each of the magnetic-field generating components (20) and past the magnetic-field sensing components (30). The magnetic-field sensing component (30) is for detecting the magnetic flux (210) that flows through the ferromagnetic object (10) as magnetic signals (55). The magnetic signal acquisition unit (150) is for acquiring data with regards the magnetic signals (55) in relation to the magnetic flux (210) detected from the ferromagnetic object (10). The magnetic signal processing unit (250) is for processing and adapting the data in a displayable format.